The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1094/phyto-99-8-0985
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Genetic, and Pathogenic Characterization of Colletotrichum acutatum, the Cause of Anthracnose of Almond in Australia

Abstract: Almond anthracnose was reported for the first time in Australia in 1998 and has since been observed in all of the major almond-growing regions. The organism causing anthracnose was confirmed as Colletotrichum acutatum using taxon-specific polymerase chain reaction (PCR). Three main morphotypes of C. acutatum from almond in Australia were identified (namely, pink, orange, and cream colony color) and the optimum temperature for mycelial growth of representative isolates was 25 degrees C. Australian isolates of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The inhibitory effect of temperature on fungi growth is variable, but most pathogens show better development at 20 to 25 °C. For C. acutatum , McKay et al [27] reported that the optimum temperature for mycelial growth was 25 °C, and Harding and Raizada [11] stated that elevated temperatures around 35.5 °C paralyze C. gloeosporioides mycelial growth, corroborating with the results obtained in this study.…”
Section: Resultssupporting
confidence: 90%
“…The inhibitory effect of temperature on fungi growth is variable, but most pathogens show better development at 20 to 25 °C. For C. acutatum , McKay et al [27] reported that the optimum temperature for mycelial growth was 25 °C, and Harding and Raizada [11] stated that elevated temperatures around 35.5 °C paralyze C. gloeosporioides mycelial growth, corroborating with the results obtained in this study.…”
Section: Resultssupporting
confidence: 90%
“…That strain was isolated together with C. acutatum and was shown to cause lesions on amond fruits in a pathogenicity test (McKay et al 2009). It was first morphologically identified as C. acutatum by the authors and recognised later as C. boninense using molecular data.…”
Section: Resultsmentioning
confidence: 99%
“…were used in a preliminary screening of the ISSR primers to identify those that generated reproducible polymorphic markers. For this purpose, 18 ISSR markers were tested: Mf‐2(AC) 8 , Mf‐5(AAC) 5 , Mf‐7(AAG) 8 , Mf‐8(AG) 8 C, Mf‐9(GACA) 4 , Mf‐10(GTG) 5 , SSR2 (ACTG) 4 , SSR10 (CAC) 5 (Villarino et al ., ; and references cited therein), (CAG) 5 , (GACAC) 3 , (GACA) 4 , (GGAT) 4 (McKay et al ., ), (GTC) 6 , (AC) 8 T (Fan et al ., ) and (TCC) 5 , (GCA) 5 , (GACG) 4 , MR (GAG GGT GGC GGT TCT) (Talhinhas et al ., ). Three primers, (ACTG) 4 , (GACG) 4 and Mf‐5(AAC) 5 (Table ), which generated the most reproducible and easily identifiable polymorphic DNA products, were selected for the analysis of all tested Monilinia spp.…”
Section: Methodsmentioning
confidence: 99%